Tegangan Residu Keping Arester sebagai Fungsi dari Cacah Keping Arester - Devia Eka Yunida (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Lightning is a natural phenomenon that usually appears during the rainy season which begins with a momentary flash of light followed by a booming voice. Indonesian territory located in the equatorial region has a tropical climate and the humidity is quite high. This is a major factor lightning formation. Research on the cutting capacity of low voltage arrester residual voltage of 220 volts is done with laboratory scale testing methods. Tests carried out using a high-voltage test equipment consisting of a series that has a specific function. Overall system testing in this study by using a series of impulse voltage generator, which serial-four arrester, voltage divider and an oscilloscope. Then start tested arresters from a single, serial two, serial three and serial four. Circuit used in testing is a series of current impulse in the Laboratory of High Voltage Engineering of Gadjah Mada University. The results of the testing showed that the more arrester serried the more the greater residual voltage of the system. So that might be expected that serial low voltage arrester can replace the function of a highvoltage arrester if necessary. Exponential formula for the amount needed to serial arrester is y = 0.694x acquired-0106.